Unrealized potential of drug repositioning in Europe during COVID-19 and beyond: a physician's perspective - A. B. Bayoumy; N. K. H. de Boer; A. R. Ansari; F. Crouwel; C. J. J. Mulder (Taylor & Francis Group, 2020)
Drug repositioning is the scientific strategy of investigating existing drugs for additional clinical indications. The advantages of drug repositioning are that it benefits patients and that it adds new indications to existing drugs for lower costs compared to de novo drug development. Clinical research groups recognizing efficacy of these "old" drugs for a new indications often face an uphill struggle due to a lack of funding and support because of poor structural and regulatory support for clinical drug development. The current framework for drug repositioning allows "venture capital" companies to abuse loopholes in the legislation to gain long-term market authorization among with excessive high pricing. A new regulatory framework is needed to prevent abuse of the legislation and promote clinical investigator-driven drug repositioning. The COVID-19 pandemic has boosted funding and regulatory support for drug repositioning. The lessons learned from the COVID-19 pandemic should be implemented in a new clear blueprint for drug repositioning. This blueprint should guide clinicians through legislation for drug repositioning in the EU. This review summarizes the routes for registration and discusses the current state of drug repositioning in Europe.